7세 연골 무형성증 남아에서 진단된 중증 폐쇄성 수면 무호흡증 1례 - 황정주(Jeongju Hwang), 서주희(Ju-Hee Seo) (Sumyŏn--chŏngsin saengni, 2020)
Obstructive sleep apnea (OSA) is a sleep-related breathing disorder in which narrowing and obstruction of the upper airway lead to frequent arousal and decreased arterial oxygenation during sleep. OSA is more common in children with genetic disorders like achondroplasia compared to children without genetic disorders. Achondroplasia is genetic disorder characterized by hypoplasia of the facial bone and skull base with foramen magnum stenosis, resulting in exceedingly high frequency of OSA. The authors present a case of a patient with achondroplasia diagnosed with severe OSA through polysomnography after adenectomy showed little therapeutic effect and who was treated with continuous positive airway pressure. 수면 무호흡증은 상기도가 좁아지거나 막히게 되면서 반복적인 수면 중 각성과 동맥내 산소포화도의 저하를 유발하는 수면관련 호흡장애이다. 이 질환은 연골무형성증과 같이 유전 질환을 가진 어린아이들에게서 상대적으로 그렇지 않은 아이들에 비해 더 취약하다. 연골무형성증은 안면골과 두개저의 형성 저하와 함께 선천적으로 대후공의 협착이 동반되는 것을 특징으로 하는 유전 질환으로 높은 빈도의 폐쇄 수면무호흡증을 나타낸다. 저자들은 연골 무형성증 환아에서 편도절제술 이후에도 지속되는 증상에 대해 수면 다원검사를 시행하여 중증 폐쇄성 수면 무호흡증 진단 및 지속기도양압 치료를 하였던 1례를 경험하였기에 문헌 고찰과 함께 보고하는 바이다.